33.3k views
1 vote
(A+B)2 =? ...........

User Eason Kang
by
5.6k points

1 Answer

4 votes

Answer

(A + B)² = (A + B) (A + B)

= A² + 2AB + B²

Explanation

(A + B)² = (A + B) (A + B)

To open this bracket or to expand this, we will use one of the two expressions to multiply the other

(A + B)(A + B) = A (A + B) + B (A + B)

= A×A + A×B + B×A + B×B

= A² + AB + BA + B²

Note that AB = BA, so, the expression is better written as

A² + AB + AB + B²

= A² + 2AB + B²

Hope this Helps!!!

User Dribbel
by
5.4k points